The current landscape of machine learning-based radiomics in arteriovenous malformations: a systematic review and radiomics quality score assessment - Grossen, Audrey A.; Evans, Alexander R.; Ernst, Griffin L.; Behnen, Connor C.; Zhao, Xiaochun; Bauer, Andrew M. (Frontiers in Neurology, 2024)
Background Arteriovenous malformations (AVMs) are rare vascular anomalies involving a disorganization of arteries and veins with no intervening capillaries. In the past 10 years, radiomics and machine learning (ML) models became increasingly popular for analyzing diagnostic medical images. The goal of this review was to provide a comprehensive summary of current radiomic models being employed for the diagnostic, therapeutic, prognostic, and predictive outcomes in AVM management.Methods A systematic literature review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines, in which search of the PubMed and Embase databases were searched using the followingincluded the search terms: (cerebral OR brain OR intracranial OR central nervous system OR spine OR spinal) AND (AVM OR arteriovenous malformation OR arteriovenous malformations) AND (radiomics OR radiogenomics OR machine learning OR artificial intelligence OR deep learning OR computer-aided detection OR computer-aided prediction OR computer-aided treatment decision) with no search filters. A radiomics quality score (RQS) was calculated for all included studies.Results ThirteenSix studies were included, which were all retrospective in nature. Three Two studies (323%) dealt with AVM diagnosis and grading, 1 study (178%) gauged treatment response, 28 (3362%) predicted outcomes, and the last one (178%) addressed prognosis. No radiomics model had undergone external validation. The mean RQS was 15.9214.85 (range: 10-18).We demonstrated that radiomics is currently being studied in different facets of AVM management. While not ready for clinical use, radiomics is a rapidly emerging field expected to play a significant future role in medical imaging. More prospective studies are warranted to determine the role of radiomics in the diagnosis, prediction of comorbidities, and treatment selection in AVM management.